Genetic mapping of quantitative trait loci for slow-rusting traits in wheat - Lu, Yue (Kansas State University, 2016)
Wheat leaf rust, caused by Puccinia triticina, is an important fungal disease worldwide. Growing resistant cultivars is an effective practice to reduce the losses caused by the disease, and using slow-rusting resistance genes can improve the durability of rust resistance in the cultivars. CI13227 is a winter wheat line that shows a high level of slow-rusting resistance to leaf rust and has been studied extensively. In this research, two recombinant inbreed line (RIL) populations derived from CI13227 x Suwon (104 RILs) and CI13227 x Everest (184 RILs) and one doubled haploid (DH) population derived from CI13227 x Lakin with 181 lines were used to identify quantitative trait loci (QTLs) for slow leaf rusting resistance. Each population and its parents were evaluated for slow-rusting traits in two greenhouse experiments. A selected set of 384 simple sequence repeat markers (SSRs), single nucleotide polymorphism markers (SNPs) derived from genotyping-by-sequencing (GBS-SNPs) or 90K-SNP chip (90K-SNPs) were analyzed in the three populations. Six QTLs for slow-rusting resistance, QLr.hwwgru-2DS, QLr.hwwgru-7BL, QLr.hwwgru-7AL, QLr.hwwgru-3B_1, QLr.hwwgru-3B_2, and QLr.hwwgru-1D were detected in the three populations with three stable QTLs, QLr.hwwgru-2DS, QLr.hwwgru-7BL and QLr.hwwgru-7AL. These were detected and validated by Kompetitive Allele-Specific PCR (KASP) markers converted from GBS-SNPs and 90K-SNPs in at least two populations. Another three QTLs were detected only in a single population, and either showed a minor effect or came from the susceptible parents. The KASP markers tightly linked to QLr.hwwgru-2DS (IWB34642, IWB8545 and GBS_snpj2228), QLr.hwwgru-7BL (GBS_snp1637 and IWB24039) and QLr.hwwgru-7AL (IWB73053 and IWB42182) are ready to be used in marker-assisted selection (MAS) to transfer these QTLs into wheat varieties to improve slow-rusting resistance in wheat.
Keywords: KASP; SNP; QTL; Slow-rustingGBS